The ascent of science. - Silver, Brian L. (Oxford University Press, 2000)
The author provides a sweeping overview of the whole of Western science, from the Renaissance to the present. In it, he translates the most important, and often impenetrably obscure, scientific developments into a vernacular that aims to be accessible and illuminating.